Land tax in the system of property taxation: specifics administration in Ukraine and EU countries - PATYTSKA, Khrystyna (Scientific journal «World of Finance», 2019)
Introduction. Problems of local budgeting in Ukraine, lack of financial resources of local authorities and instability of their revenue have been quite topical and still unsolved. Like most countries that emerged from the former Soviet Union, Ukraine has faced very substantial difficulties in maintaining economic growth while at the same time organizing an effective local government and fiscal structure and administration. An important aspect of this task has been to establish clearly defined property rights, including those in land, in order to facilitate market activities while also providing an appropriate fiscal base for local government. Purposes. The article is devoted to the problem of the formation of local authorities’ financial resources, local taxes and dues being their main source including land tax, to the process of formation of land taxation as well as to the definition of its role in the system of functioning of local authorities and state on the whole. The paper contains a comprehensive analysis of land taxation system, and shows its role and place in the state’s economic system. Proceeding from the analysis of the existing practice of land tax levying the author proves the necessity to reform land taxation, improve the mechanisms of levying land tax to insure full and timely income of land tax to local budgets. Results. Nature and structure of land taxation mechanism were proved and approaches concerning it construction in Ukraine were developed. Based on the realized analysis principal trends of collecting land tax in Ukraine were clarified, main factors which have the effect on forming of land taxation mechanism in our state were determined, problem aspects in land taxation which require improvement were emphasized. The mechanism of land tax application in foreign countries was investigated, main directions of land taxation processes optimization in Ukraine were proposed. It is proposed the improving the procedure for administering land tax in terms of conducting normative monetary valuation of land. Conclusions. It was proposed to improve the land tax in the area of its administration and the establishment of tax rates. The author has suggestions and proposals regarding legislation improvement in the sphere of legal regulation of land valuation in Ukraine.